Unraveling the Genotypic and Phenotypic Diversity of the Psychrophilic Clostridium estertheticum Complex, a Meat Spoilage Agent - Wambui, Joseph; Stevens, Marc J. A.; Cernela, Nicole; Stephan, Roger (Frontiers in Microbiology, 2022)
The spoilage of vacuum-packed meat by Clostridium estertheticum complex (CEC), which is accompanied with or without production of copious amounts of gas, has been linked to the acetone-butyrate-ethanol fermentation, but the mechanism behind the variable gas production has not been fully elucidated. The reconstruction and comparison of intra- and interspecies metabolic pathways linked to meat spoilage at the genomic level can unravel the genetic basis for the variable phenotype. However, this is hindered by unavailability of CEC genomes, which in addition, has hampered the determination of genetic diversity and its drivers within CEC. Therefore, the current study aimed at determining the diversity of CEC through comprehensive comparative genomics. Fifty CEC genomes from the current and previous studies from 11 CEC species were compared. Recombination and gene gain/loss events were identified as important sources of natural variation within CEC, with the latter being pronounced in genomospecies2 that has lost genes related to flagella assembly and signaling. Pangenome analysis revealed variations in carbohydrate metabolic and hydrogenases genes within the complex. Variable inter- and intra-species gas production in meat by C. estertheticum and C. tagluense were associated with the distribution of the [NiFe]-hydrogenase hyp gene cluster whose absence or presence was associated with occurrence or lack of pack distention, respectively. Through comparative genomics, we have shown CEC comprises of 11 species that exhibit high genetic diversity that can be partly attributed to recombination and gene gain/loss events. We have also shown genetic basis for variable gas production in meat can be attributed to the presence/absence of the hyp gene cluster.